Risk Aversion, Performance Pay, and the Principal-Agent Problem - Haubrich, Joseph G. (Journal of Political Economy, 1994)
This paper calculates numerical solutions to the principal-agent problem and compares the results to the stylized facts of CEO compensation. The numerical predictions come from parameterizing the models of Grossman and Hart and of Holmstrom and Milgrom. While the correct incentives for a CEO can greatly enhance a firm's performance, providing such incentives need not be expensive. For many parameter values, CEO compensation need increase only by about $10 for every $1,000 of additional shareholder value; for some values, the amount is 0.003 cents.